Periconceptional nonsteroidal anti‐inflammatory drug use, folic acid intake, and the risk of spina bifida. Issue 17 (3rd August 2021) - Esposito, Daina B.; Parker, Samantha E.; Mitchell, Allen A.; Tinker, Sarah C.; Werler, Martha M.
Abstract: Background: Use of nonsteroidal anti‐inflammatory drugs (NSAIDs) during pregnancy may increase risk for neural tube defects (NTDs), including spina bifida. Folic acid intake can prevent NTDs, but it is not known whether it modifies any risks associated with NSAID use. Objectives: To assess the impact of periconceptional NSAID use on the risk of spina bifida overall and stratified by folic acid intake. Study Design: We analyzed 1998–2015 data from the Slone Epidemiology Center Birth Defects Study, a multi‐site, case–control study. Mothers were interviewed to identify sociodemographic factors, behaviors, and exposures during pregnancy. Periconceptional NSAID use was defined as use of aspirin, ibuprofen, naproxen, or COX2 inhibitors within the month before or after the last menstrual period. Logistic regression models were used to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs) for NSAID use, adjusted for study center and race/ethnicity stratified by average daily folic acid intake above ("high FA") or below ("low FA") 400 mcg/day. Results: We compared mothers of 267 infants with spina bifida to mothers of 6, 233 nonmalformed controls. Among control mothers, 20% used NSAIDS periconceptionally (16% ibuprofen, 4% aspirin, 3% naproxen, and <1% COX‐2 inhibitors). For any NSAID use, the aORs among low FA and high FA women were 1.70 (95% CI [1.13, 2.57]) and 1.09 (95% CI [0.69, 1.71]), respectively. Conclusions: We observed a small increase in the risk for spina bifida among infants born to women who used NSAIDs periconceptionally, but this risk was limited to those who had inadequate folic acid intake.